Alignment of atomic inner-shells following alpha-decay-induced ionization - McConnell, Sean R.; Artemyev, Anton; Surzhykov, Andrey (Journal of physics. B, Atomic, molecular and optical physics, 2011)
Nuclear alpha decay may induce the emission of electrons originally bound to the nucleus. If the ejected electron initially resides in a state with the total angular momentum j > 1/2, the residual ion may be aligned. In this theoretical analysis, we pay particular attention to the alignment following LIII shell ionization. Focus has also been given to the effects of shake-off, recoil and nuclear potential screening. To illustrate these effects, we have performed calculations on neutral atoms of 210Po and 228Th nuclei, subject to their respective alpha decay, over a range of commonly encountered alpha particle kinetic energies (ϵα ∼ O(10 MeV)).